Synthesis of Distally‐Bridged Chiral Resorcinarene Crowns. - Mocerino, Mauro; Tan, Daniel A; McIldowie, Matthew J; Massera, Chiara (Wiley-Blackwell, 2020)
Our interest in the potential of chiral tetramethoxy-resorcinarene as agents for chiral recognition has led us to synthesise twelve distally-bridged chiral resorcinarene crowns. The fascinating architecture of these partially-enclosed chiral basket molecules is evident in the solid-state structures which have been determined by single crystal X-ray crystallography. Moreover, the enantiomers of these chiral resorcinarene crowns have been resolved via diastereomeric resolution, with the absolute configuration of the diastereomers being determined by X-ray crystallography. This work enables further exploration of these enantio-pure chiral baskets as possible chiral resolving agents.